The Pembroke Site: Thule Inuit Migrants on Southern Victoria Island - Friesen, T. Max; Norman, Lauren E.Y. (ARCTIC, 2016)
This paper presents description and interpretation of the Pembroke site, the earliest known Thule Inuit occupation in the southeastern Victoria Island region, Nunavut. The site has 11 extant dwellings, including five heavy tent rings, five light semi-subterranean dwellings, and a qalgiq (large communal structure). The site’s economy revolved mainly around the acquisition of caribou, Arctic char, and lake trout, with minimal consumption of sea mammals. Radiocarbon dates, reinforced by artifact analyses, indicate an occupation around AD 1400. Based on several lines of evidence, including the extremely small artifact samples, the site is interpreted as having been occupied relatively briefly. It represents the first colonization of the region by Thule people, approximately 200 years after the initial Thule migration from Alaska into the eastern Arctic. Thus, it documents a second migration wave: an expansion of Thule peoples from their initially occupied territories to other, in some ways less optimal, regions Cet article présente la description et l’interprétation du site de Pembroke, le plus ancien lieu d’occupation des Inuits thulés dans le sud-est de la région de l’île Victoria, au Nunavut. Ce site compte 11 habitations historiques, dont cinq cercles de tentes imposantes, cinq habitations légères enterrées et un qalgiq (grande structure collective). L’économie du site reposait surtout sur l’acquisition du caribou, de l’omble chevalier et de la truite de lac. La consommation de mammifères marins était minime. La datation au carbone 14, renforcée par l’analyse d’artefacts, indique que l’occupation a eu lieu vers 1400 apr. J.-C. D’après plusieurs sources de données, dont les échantillons d’artefacts extrêmement petits, le site est interprété comme ayant été occupé pendant une période relativement brève. Il représente la première colonisation de la région par le peuple des Thulés, environ 200 ans après la toute première migration des Thulés de l’Alaska jusqu’à l’est de l’Arctique. Ce site témoigne donc d’une ...